1876 Miss. Laws 131, 134 - (:unkn) unknown (My University, 1876)
Ch. 304: Allowed the Auditor of Public Accounts to create assessment rolls for property subject to taxation, including pistols, dirks, bowie knives, and sword canes.
Keywords: TAX - PROPERTY OR SALES